VD_FINDINFO Faillite / 2011 / 75 vom 20. Januar 2012 - VD Tribunal cantonal (2012)
DÉLAI DE RECOURS, MOTIF DU RECOURS, CONDITION DE RECEVABILITÉ, ACTE DE RECOURS | 174 al. 1 LP, 149 CPC (CH), 321 al. 1 CPC (CH), 321 al. 2 CPC (CH)